Clinical characteristics and survival of second primary breast carcinoma with extramammary malignancies - Jing, Yaoyao; Wang, Xiaofang; Sun, Bei (Frontiers in Oncology, 2023)
Objectives To investigate the characteristics, diagnosis, survival and prognosis of second primary breast carcinoma (SPBC). Materials and methods Records of 123 patients with SPBC in Tianjin Medical University Cancer Institute & Hospital between December 2002 and December 2020 were retrospectively reviewed. Clinical characteristics, imaging features and survival were analyzed and comparisons between SPBC and breast metastases (BM) were made. Results Of 67156 newly diagnosed breast cancer patients, 123 patients (0.18%) suffered previous extramammary primary malignancies. Of the 123 patients with SPBC, approximately 98.37%(121/123)were female. The median age was 55 years old (27-87). The average diameter of breast mass was 2.7 cm (0.5-10.7). Approximately 77.24% (95/123) of the patients presented with symptoms. The most common types of extramammary primary malignancies were thyroid, gynecological cancers, lung, and colorectal. Patients with the first primary malignant tumor of lung cancer were more likely to develop synchronous SPBC, and those with the first primary malignant tumor of ovarian cancer were more likely to develop metachronous SPBC. When comparing with BM, patients with SPBC were more often older (≥45 years old), at earlier stages (I/II), more microcalcification and less multiple breast masses in imaging. More than half (55.88%) of patients in the metachronous group developed primary breast cancer within 5 years after diagnosis of extramammary primary cancer. The median overall survival time was 71 months. Within 90 months, the prognosis of patients with synchronous SPBC was worse than that of patients with metachronous SPBC (p=0.014). Patients with BM had the worst outcome compared with patients with synchronous SPBC and metachronous SPBC (p<0.001).ER/PR-negative status, an interval of less than 6 months between the onset of two tumors, a late stage of first primary malignancy, and an age of diagnosis of first primary malignancy greater than 60 years predicted a worse prognosis for patients with SPBC. Conclusion The possibility of SPBC should be considered during the follow-up of patients with primary extramammary malignancy, especially within 5 years of the onset of the first tumor. The stage of first primary malignancy and the age at diagnosis of first primary malignancy have an impact on the prognosis of patients with SPBC.